2022
DOI: 10.20944/preprints202203.0230.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimised Design of An Arterial Network Model Reproduces Characteristic Central and Peripheral Hemodynamic Waveform Features in Young Adults

Abstract: The arterial network in healthy young adults is thought to be structured to minimise wave reflection in conduit arteries, producing an ascending aortic pressure waveform with three key features: early systolic peak, negative systolic augmentation, and diastolic hump. One-dimensional computer models have provided significant insights into arterial haemodynamics, but no previous models of the young adult have exhibited these three features. Since the latter was likely to be related to unrepresentative or non-opt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…To assess the accuracy of these methods using a GTRT, every individual backward wave arriving at the ventricle must be tracked; this can only be achieved through computational methods. We recently developed and validated a non-linear one-dimensional model of the systemic arterial circulation of a young adult-the 'YoungAdult' model-the details of which are described elsewhere (27). In brief, a two-chamber heart model served as the input to the systemic arterial circulation, and distal arteries were terminated with 3-element windkessels representing vascular beds.…”
Section: Linear Modelmentioning
confidence: 99%
“…To assess the accuracy of these methods using a GTRT, every individual backward wave arriving at the ventricle must be tracked; this can only be achieved through computational methods. We recently developed and validated a non-linear one-dimensional model of the systemic arterial circulation of a young adult-the 'YoungAdult' model-the details of which are described elsewhere (27). In brief, a two-chamber heart model served as the input to the systemic arterial circulation, and distal arteries were terminated with 3-element windkessels representing vascular beds.…”
Section: Linear Modelmentioning
confidence: 99%
“…Therefore, all bifurcations and junctions in the large arteries were carefully matched through to a mismatched interface between terminal arteries and their downstream vascular beds. This assumption may have contributed to the model limitations, such as lack of the typical pressure amplification in the limbs that has been demonstrated previously by many investigators and confirmed by Kondiboyina et al., 2022 in their small validation sample (Kondiboyina et al., 2022). For example, their Table 2 shows that model systolic and pulse pressures fall between brachial and radial and between femoral and posterior tibial arteries whereas corresponding values increase in the validation sample.…”
mentioning
confidence: 90%
“…Innovations incorporated by Kondiboyina et al, 2022 into the 'YoungAdult' model are commendable and will advance the field. However, assumptions enforced when initializing the model require thought and Perspective J Physiol 600.20 must reflect key empirical observations, such as pressure amplification.…”
mentioning
confidence: 99%
See 2 more Smart Citations